ANALISIS PENGARUH DER CR DAN TATO TERHADAP PBV DENGAN ROA SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Properti dan Real Estate yang Terdaftar pada BEI Tahun 2011 – 2014) - Misran, Medy; Chabachib, Mochamad (Diponegoro Journal of Management, 2017)
The aim of this research is to identify and analyze the determinant of Price to Book Value  (PBV)  in  Property  and  Real  Estate  Firm  which is  listed  on  Indonesia  Stock Exchange (IDX) period of 2011-2014. Price to Book Value (PBV) is dependent variabel in this research. There are three independent variables that used, which are Debt to Equity Ratio, Current Ratio, Total Asset Turnover, and an intervening variabel which is Return on Asset.The population used in the study is all companies engaged in Property and Real Estate Firm which is listed on Indonesia Stock Exchange (IDX) period of 2011-2014. Therefore  total  population  obtained  is  35  companies.  Sampling  in  this  study  using purposive sampling which resulted in a sample into 26 companies of Property and Real Estate sectors. Data analysis method used multiple linear regression analysis and using classical assumption test with path analysis using SPSS program.The result of this research show that Current Ratio (CR) has negative influance not significant  to  Price  to  Book  Value  (PBV),  Debt  to  Equity  Ratio  (DER),  Total  Asset Turnover (TATO), and Return on Asset (ROA) have positive influance significant to Price to Book Value (PBV). Return on Asset (ROA) can mediate influance beetwen variable independent Debt to Equity Ratio (DER) andTotal Asset Turnover (TATO) to Price to Book Value (PBV). But Return on Asset (ROA) can not mediate influance beetwen Current Ratio (CR) to Price to Book Value (PBV).